Liver functions in patients with obstructive sleep apnea syndrome - Beyhan Sağmen, Seda; Torun Parmaksız, Elif; Şener Cömert, Sevda; Fidan, Ali; Salepçi, Banu (The European Research Journal, 2018)
Objective: Previous studies showed that obstructive sleep apnea syndrome (OSAS) was associated with liver diseases such as elevated liver enzyme levels and hepatic steatosis. The aim of this study was to assess the relationship between serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels and OSAS and its severity. Methods: A total of 617 patients who underwent PSG (polysomnography) between January 2016 and May 2017 were evaluated in this study. AST, ALT, total cholesterol, triglyceride levels and body mass index were analyzed. The data were analyzed using the Student t-test, ANOVA, Chi-square test, and Pearson’s correlation coefficient. Results: Five hundreds and thirty patients with OSAS and 60 healthy controls were included in the study. Of the patients in the OSAS group, 17.7% had an elevated ALT level and 7.9% had an elevated AST level. There was a statistically significant difference in ALT and AST levels between the OSAS and control groups (p < 0.001 and p < 0.001, respectively). In the OSAS group, there was a statistically significant positive relationship between serum ALT and AST levels and apnea-hypopnea index (AHI), apnea index, oxygen desaturation index. Both AST and ALT levels were statistically significantly higher in obese patients than in non-obese patients (p < 0.001 and p < 0.001, respectively). ALT level was statistically significantly higher in patients without hypertension than in patients with hypertension (p < 0.001). In OSAS patients without hypertension, there was a statistically significant relationship between serum ALT and AST levels and AHI (r = 0.223, p < 0.001 and r = 0.142, p = 0.007; respectively). Conclusion: OSAS is a risk factor for elevated liver enzyme levels. Hypoxia plays an important role on liver enzymes in OSAS patients.